River of life, river of death: the Ganges and India's future - Mallet, Victor (Oxford University Press, 2017)
"Cover " -- "RIVER OF LIFE, RIVER OF: The Ganges and Indiaâs Future" -- "Copyright" -- "Dedication" -- "Acknowledgements" -- "Contents" -- "List of Plates" -- "Note on Spelling" -- "Preface" -- "Map of the Ganges" -- "1: Introduction: Killing the Mother Goddess" -- "2: Mouth of the Cow: The Himalayan Source" -- "3: Holy Waters" -- "4: How to Build a Megacityâand Save the Ganges" -- "5: Varanasi: Indiaâs Capital for a Day" -- "6: Varanasi: Broken Promises" -- "7: Toxic River" -- "8: Superbug River" -- "9: Dolphins, Crocodiles, and Tigers" -- "10: People Pressure: Why Population Growth Is Not a Dividend" -- "11: Water and Wells: Why the Taps Run Dry" -- "12: Dams and Droughts: Engineering the Ganges" -- "13: A Bollywood Star: Ganga on Film" -- "14: Exotic River: Foreigners on the Ganges" -- "15: Storms and Sandbanks: Boats on the Ganges" -- "16: Trade Artery No More: Calcutta and Bengal" -- "17: Mission Impossible?: How to Clean the Ganges" -- "18: Beautiful Forest: Where Ganga Meets the Ocean" -- "Notes" -- "Chapter 1" -- "Chapter 2" -- "Chapter 3" -- "Chapter 4" -- "Chapter 5" -- "Chapter 6" -- "Chapter 7" -- "Chapter 8" -- "Chapter 9" -- "Chapter 10" -- "Chapter 11" -- "Chapter 12" -- "Chapter 13" -- "Chapter 14" -- "Chapter 15" -- "Chapter 16" -- "Chapter 17" -- "Chapter 18" -- "Bibliography" -- "Publisherâs Acknowledgements" -- "Picture Acknowledgements